Taxonomic redescription and molecular confirmation of Lutjanus rufolineatus (Acanthuriformes: Lutjanidae) from the Andaman Islands, India - Ps, Fahmeeda Parveen; Arjunan, Jayaraj K; Venu, Sasidharan; Eranhottu, Shibin; Ummath, Ameen; Kalita, Samrat; Pv, Mohammed Ramees; Sadaka, Shehin (Zootaxa, 2025)
We provide a detailed taxonomic redescription of Lutjanus rufolineatus, based on six specimens collected from the Andaman Islands, India. The species’ taxonomic status and distribution have historically been misinterpreted within Indian waters due to close similarities with congeners, leading to frequent misidentification. To address this, we performed comprehensive morphological and molecular analyses, including DNA barcoding and phylogenetic reconstruction, to confirm the identity of L. rufolineatus and clarify its relationships with related species. Our findings emphasize the value of thorough taxonomic assessment in delineating species boundaries, particularly for understudied marine fauna. Additionally, this research fills critical gaps in the taxonomy of Indian marine fishes, addressing past ambiguities and enhancing regional biodiversity records. By integrating morphological and molecular data, this study underscores the importance of precise species identification for improved biodiversity conservation and management efforts in the Indo-Pacific.